Natural Resources Depletion, Renewable Energy Consumption and Environmental Degradation: A Comparative Analysis of Developed and Developing World - Ali, Amjad; Audi, Marc; Roussel, Yannick (International Journal of Energy Economics and Policy, 2021)
This article investigates the impact of renewable energy consumption and natural resource depletion on environmental degradation from 1990 to 2014. The analysis of this study is distributed into three parts, developing country analysis, developed country analysis and complete sample analysis. An insignificant relation has found between natural resource depletion and environmental degradation in the case of complete sample analysis and developing country analysis, but vice-versa in developed countries. Fossil fuel energy consumption has a positive and significant impact on environmental degradation in developing countries. Renewable energy consumption has negative impact on environmental degradation in the case of complete sample analysis and developed country analysis, but visa-versa in developing countries. Economic growth positively and significantly effecting environmental degradation in all the three cases, this mean for higher economic growth we have to bear some environmental degradation. But it is the need of the hour that we should find some threshold between economic growth and pollutant emissions, so that a healthy environment can be safe for coming generations. So, for a healthy environment, fossil fuel consumption should be reduced and consumption of renewable energy with merchandised trade and urbanization can be encouraged. Keywords: environmental degradation, natural resources, economic growth, renewable energy, JEL Classifications: Q57, Q26, F43, Q20 DOI: https://doi.org/10.32479/ijeep.11008